PENGARUH PENGGUNAAN MEDIA VIDEO ANIMASI TERHADAP MOTIVASI BELAJAR SISWA TUNAGRAHITA PADA PEMBELAJARAN TIK DI SLB ASUHAN KASIH KUPANG - Tabala, Yudi Erwina; Khatrin J. Taku Neno; Jhon Enstein (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using animated video media on the learning motivation of mentally retarded students in Information and Commnication Technology (ICT) subjects at SLB Asuhan Kasih Kupang. This type of research is quantitative experimental with One – Group Pretest – Posttest Design. The research sample consisted of 11 mild mentally retarded students of class X SMALB. The data collection instrument was a learning motivation questionnaire given before (pre – test) and after (post – test)  treatment. The results of data analysis using Paired Samples T – Test showed a value of . (2 – tailed) = 0.000 < 0.05, which means there is a significant effect of using animated video media. The average value of student learning motivation increased from 56.97 (fair category) to 93.54 (very good category). Thus, the use of animated video media is proven to be effective in increasing the learning motivation of mentally retarded students in ICT learning.